The Intention to Adopt Green Pesticide Among Oil Palm Planters: Review of The Extant Literature - Mohammed Nizar Khir Azman; Bamini KPD Balakrishnan (MPOB, 2023)
Pests and diseases can cause costly and irreparable harm to crops, especially oil palm. There are many methods that planters can adopt to manage them, and green pesticides can serve as an alternative solution. Preliminary research is carried out by adopting the theory of planned behaviour or TPB [attitude, subjective norms and perceived behavioural control (PBC)] for a sound conceptual framework. This paper, therefore, investigates the determinant factors affecting Malaysian oil palm planters to adopt green pesticides. A comprehensive literature review was used as the methodology. The Malaysian Sustainable Palm Oil (MSPO) was proposed as a moderator to optimise the planters’ intention. Overall, 12 research propositions, recategorized in TPB, were discussed in this paper and identified as the factors affecting the oil palm planters’ intention to adopt green pesticides. The proposition will lead to future empirical findings which are anticipated to facilitate the industrial transition toward utilizing environmentally friendly pesticides.